From Oblique Thrust to Strike-Slip Fault: Progressive Stages of an Accretionary Wedge Development - Martin Šuťjak; Rostislav Melichar; Ivo Baroň; Yi-Chin Chen; Jan Černý; Jia-Jyun Dong; Václav Dušek; Filip Hartvich; Jan Klimeš; Lenka Kociánová; Tùng Nguyễn; Vladimír Opletal; et al. (Lithosphere)
Accretionary wedges of orogenic belts develop differently based on the direction of thrusting, which can be perpendicular to oblique to the belt. In the case of oblique thrusting, stress partitioning occurs, which dissects the accretionary wedge, changes the tectonic regime from thrusting to strike-slip, and causes the external parts to rotate laterally. The relationship between stress partitioning and external rotation is not yet fully understood and has typically been studied separately. This study investigates the Falkenstein-Mikulov fault zone in the Outer Western Carpathians (OWC) wedge as an illustrative example of the relationship between partitioning and rotation. Using a prominent limestone marker horizon and a multidisciplinary approach—including geomorphological analysis, geological mapping, paleostress analysis, and shallow and deep-seismic geophysical surveys—we defined the fault zone’s unique arcuate geometry and identified several stages of tectonic activity. Paleostress inversion reveals multiple tectonic phases highlighting a transition from thrusting to strike-slip faulting. After thrusting (Phase D1), transversal strike-slip faults segmented the wedge coinciding with significant counterclockwise rotational patterns (Phase D2). Finally, during Phase D3, an arcuate strike-slip fault zone parallel to thrusting direction evolved, also revealing rotation of 12° over a distance of 10 km. These phases interplayed in the accretionary wedge at the same time, and their apparent succession is the result of shifting of the tectonic activity during the progressive development of the wedge. Thus, the thrusting activity in the front of the wedge was followed by rotational motion along the lateral ramps and finalized by parallel strike-slip faulting. This model explains how accretionary wedges undergo external rotation due to curved strike-slip faulting in the final stages of thrusting and has significant implications for understanding the broader tectonic evolution of accretionary wedges worldwide.